1981
DOI: 10.1351/pac198153030627
|View full text |Cite
|
Sign up to set email alerts
|

Template polymerization

Abstract: Template polymerizations (TP) are divided into two types. In type Iwe are concerned with initiation and propagation of monomer preadsorbed by or complexed to template macromolecules. In type II active oligomers created in "free" solution complex with template macromolecules and continue to propagate along the template by adding monomer "picked up" from the surrounding solution. The discussion is confined chiefly to two systems, viz, the radical TP of methylmethacrylate (MMA) along isotactic poly-MMA and that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 9 publications
0
52
0
Order By: Relevance
“…The very general concept of this process, inspired by the natural routes to nucleic acids and proteins as in the basics of the Central Dogma of Synthetic Biology is to use a template directed synthesis of macromolecules from their monomers [141][142][143][144] involving the molecular recognition, ligation, and product dissociation steps [145]. By using template polymerization of synthetic monomers onto biological templates, bioartificial polymeric blends with a higher degree of miscibility between the two components than by simple mixing of pre-formed polymers are obtained [146,147].…”
Section: Not-conventional Approaches Towards Nanoscale Tailoring Of Bmentioning
confidence: 99%
“…The very general concept of this process, inspired by the natural routes to nucleic acids and proteins as in the basics of the Central Dogma of Synthetic Biology is to use a template directed synthesis of macromolecules from their monomers [141][142][143][144] involving the molecular recognition, ligation, and product dissociation steps [145]. By using template polymerization of synthetic monomers onto biological templates, bioartificial polymeric blends with a higher degree of miscibility between the two components than by simple mixing of pre-formed polymers are obtained [146,147].…”
Section: Not-conventional Approaches Towards Nanoscale Tailoring Of Bmentioning
confidence: 99%
“…Up till now, there have been several reports on controlling the stereospecificity of poly(alkyl methacrylate)s by radical polymerization, in the presence of Lewis acids or fluoroalcohols [1]. In the 1970s, Challa et al [2] reported a stereospecific radical polymerization of methyl methacrylate (MMA) in the presence of tactic PMMAs in suitable solvents. In their cases, st-PMMA propagated in the presence of it-PMMA, and the polymerization of MMA in presence of it-PMMA afforded st-PMMA, particularly at the beginning of the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…[19,22,23] In a zip mechanism the affinity of the monomer for the template repeating unit is high (strong ionic interactions may result), the monomer molecules are adsorbed on the template and the adjacent molecules bind themselves each other (in the case of a step polymerisation) or they add to the active ends of the chain (in the case of a chain polymerisation).…”
Section: Introductionmentioning
confidence: 99%
“…[19] In particular the changes in the polymerisation rate (with respect to blank polymerisation) when the template concentration [T] changes and the monomer concentration [M] is kept constant are studied. The relative initial polymerisation rate V R = V/V B (where V is the rate template polymerisation and V B is the rate of the blank polymerisation) is reported as a function of the initial template unit to monomer molar ratio ([T]/[M]).…”
Section: Introductionmentioning
confidence: 99%